Menumbuhkan Minat Baca Sejak Dini di Taman Baca Masyarakat - M. Arif Khoiruddin; Imam Taulabi; Ali Imron (Journal An-Nafs: Kajian Penelitian Psikologi, 2016)
Reading is the capital key in progressing a nation, therefore, interest in reading must be grown in the community from an early age. Reading park community is an ideal place as an idea to play, learning and development of reading interest. Therefore, the introduction of reading park community in children from an early age discourse that presents books to children is one way to foster interest in reading for children. By growth habit of reading can boost the quality life-style, creativity, independence, struggle effort, and competitiveness next time. That reading park community can be a medium in promoting interest in reading for early childhood do several activities, namely: activities cooking contest, a bazaar of books and used clothing, drawing, coloring contest, reading stories and storytelling, training reading stories and storytelling for parents. In addition, there is a series of structuring reading park community for example, the addition of facilities and infrastructure, adding books to children, reading the management of park management system, organizing Reading Park, the design of the room. Such steps undertaken to encourage children and parents to come to the park to read, with their coming in the park to read, they know that there are many sources of interesting reading, with their interest in books and other reading materials are expected to encourage children to love reading